Transfer of continuous manufacturing process principles for mAb production in a GMP environment: A step in the transition from batch to continuous. (26th April 2022) - Botelho Ferreira, Kevin; Benlegrimet, Asma; Diane, Gabriel; Pasquier, Victor; Guillot, Raphael; De Poli, Marc; Chappuis, Loïc; Vishwanathan, Nandita; Souquet, Jonathan; Broly, Hervé; Bielser, Jean‐Marc
Abstract: Implementation of continuous in lieu of batch upstream processing (USP) and downstream process (DSP) for the production of recombinant therapeutic protein is a significant paradigm change. The present report describes how the first kilograms of monoclonal antibody were produced with equipment originally designed for batch operations while using continuous manufacturing processes and principles. Project timelines for the delivery of clinical material have driven this ambition and helped the transition. Nevertheless, because of equipment availability, a tradeoff between the envisaged continuous downstream process (cDSP) operations and the ones described in this article had to be taken. A total of 2.1 kg of monoclonal antibody were produced in two GMP runs for clinical trials. For USP, a 200‐L single‐use pilot scale bioreactor was upgraded to enable perfusion operation. DSP steps were designed to be easily transferable to cDSP for later clinical or commercial productions. An in‐line conditioning buffer preparation strategy was tested in a discontinuous way to prove its efficiency and the purification cascade was structured in parallel to the continuous collection of antibody‐containing cell culture supernatant. This strategy will avoid any process change when later moving to the continuous equipment that is currently under qualification. Alignment between small‐scale references runs and the GMP runs in terms of productivity and quality confirmed that the presented approach was valid. Thus, we demonstrate that existing fed‐batch infrastructure can be adapted to continuous manufacturing without significant additional investments. Such approach is useful to evaluate next‐generation manufacturing processes before making large investments.